Recruitment Strategies and Lessons Learned from the Children's Healthy Living Program Prevalence Survey - Julianne M. Power; Travis Fleming; Emihner Johnson; Daisy Gilmatam; Moria Shomour; Cecilia Sigrah; Mark Acosta; Marie K. Fialkowski; Ashley Yamanaka; Kathryn L. Braun; Jean Butel; Reynolette Ettienne; et al. (AIMS Press, 2016)
The US Affiliated Pacific region's childhood obesity prevalence has reached epidemic proportions. To guide program and policy development, a multi-site study was initiated, in collaboration with partners from across the region, to gather comprehensive information on the regional childhood obesity prevalence. The environmental and cultural diversity of the region presented challenges to recruiting for and implementing a shared community-based, public health research program. This paper presents the strategies used to recruit families with young children (n = 5775 for children 2 - 8 years old) for obesity-related measurement across eleven jurisdictions in the US Affiliated Pacific Region. Data were generated by site teams that provided summaries of their recruitment strategies and lessons learned. Conducting this large multi-site prevalence study required considerable coordination, time and flexibility. In every location, local staff knowledgeable of the community was hired to lead recruitment, and participant compensation reflected jurisdictional appropriateness (e.g., gift cards, vouchers, or cash). Although recruitment approaches were site-specific, they were predominantly school-based or a combination of school- and community-based. Lessons learned included the importance of organization buy-in; communication, and advance planning; local travel and site peculiarities; and flexibility. Future monitoring of childhood obesity prevalence in the region should consider ways to integrate measurement activities into existing organizational infrastructures for sustainability and cost-effectiveness, while meeting programmatic (e.g. study) goals.